Designing and Applying Web Assisted Activities to be Used in Flipped Classroom Model - Murat Cetinkaya (Institute of Advanced Engineering and Science, 2017)
The purpose of this study is to develop personalized web assisted activities for the flipped classroom model applied in the “Human and Environment Interactions” unit of science lesson and to research its effect on students’ achievement. The study was conducted with the participation of 7th grade science lesson students (N=74) within a period of 3 weeks. In the study, one of the experimental research methods, quasi-experimental research method, was used. Two different classes were randomly assigned as the experimental and control groups and flipped classroom model was applied on both groups. In the control group, only video lessons were used before the lesson. In the experimental group, web assisted activities were used as well as video lessons both before and during the lessons. “Human and Environment Interactions Unit Achievement Test”, which had a reliability coefficient of (KR-20) 0.76, was applied on the groups. The data analyses showed that there was a positive significant difference in favor of experimental group students. The developed material developed can be re-organized for any subject of the science class.